Systematic review of the value-driven attentional capture paradigm in visual attention studies: Evidence from 52 experiments - Miloš Stanković (Acta Psychologica)
Human visual attention is strongly influenced by rewards, affecting both top-down and bottom-up attentional processes. The value-driven attentional capture (VDAC) paradigm, introduced by Anderson et al. (2011b), has had a significant impact on the field of visual attention. In particular, it has facilitated scientific understanding of how a previously task-irrelevant stimulus (e.g., a red circle) paired with monetary or social rewards can capture attention when presented as a distractor (e.g., red) in subsequent non-reward shape-search tasks (e.g., diamond). However, recent work using the traditional VDAC paradigm has produced controversial research findings. The present systematic review, including 23 publications (52 experiments), investigated whether a) reward-associated features might influence attentional capture subsequently, and b) the VDAC paradigm provides a reliable experimental approach to examine the reward-attention relationship. The analysis of these VDAC experiments has revealed methodological concerns, including history-selection confounds, issues with color-reward associations, color-luminance effects and preferences, and low statistical power. Reward-associated features influence attentional capture, however, the current VDAC paradigm provides weak experimental effects. Critically, the literature review provides a concise evaluation of the VDAC paradigm and offers potential directions for further experimental research.